Comparison of two doses of ketoprofen to treat pain: a double‐blind, randomized, noninferiority trial. (3rd September 2012) - Riou, Bruno; Plaisance, Patrick; Lecomte, François; Soulat, Louis; Orcel, Philippe; Mazoit, Jean‐Xavier
Abstract The aim of our study was to compare the efficacy and safety of two doses of ketoprofen (200 mg vs. 300 mg/day) in ambulatory emergency patients with pain related to traumatic and nontraumatic bone and joint diseases. We tested the hypothesis that the efficacy of the lower dose was not lower than that of the higher dose in a double‐blind, randomized, noninferiority trial. Patients included in the study were aged 18–65 years with closed benign trauma of the motor system or acute noninfectious rheumatologic conditions, with a resting pain intensity ≥3/10 on a numeric pain scale (NPS), requiring ketoprofen for 5 days. The main end‐point was based on two efficacy co‐criteria: (i) mean change from baseline of resting pain intensity at the end of the day over 5 days and (ii) total intake of concomitant analgesics. We included 409 patients: 200 in the 200‐mg group and 209 in the 300‐mg group. The mean change in pain intensity at rest (difference between groups: 0.0, 95% CI −0.4 to 0.4; P = 1.00) and in analgesic consumption (difference between groups: −0.6, 95% CI −1.9 to 0.6; P = 0.33) was not significantly different between the two groups, and the differences were lower than the predefined inferiority margins (0.5 and 1.5, respectively), thus demonstrating noninferiority. No significant difference was noted in the incidence of adverse events (21% vs. 20%, P = 0.71). The efficacy of the 200‐mg daily dose of ketoprofen in relieving pain in emergency cases was not inferior to that of the 300‐mg dose.